Application of SVC on stabilizing torsional oscillations and improving transient stability - Abdou, A.; Abu-Siada, Ahmed; Pota, H. (IEEE, 2012)
This paper investigates the use of static var compensator (SVC) to stabilize multi-mode torsional oscillations of sub-synchronous resonance (SSR) of a large turbine generator set and to improve the system transient stability. In this context, the study is performed on a detailed nonlinear model for system-1 of the second IEEE benchmark for computer simulation of sub-synchronous resonance using EMTDC/PSCAD. The voltage at the machine terminals along with the generator shaft speed are used to control the number of SVC capacitors which are switched on or off and to generate a proper firing angle for the SVC thyristors to control the reactive power exchange between the AC system and the SVC. Results show that the proposed controller is very effective in damping all SSR modes of the system under study. The proposed controller is efficient, simple, cost effective and easy to implement.